Autophagic, apoptotic, and necrotic cancer cell fates triggered by acidic pH microenvironment. Issue 7 (4th December 2018) - Rabiee, Shadi; Tavakol, Shima; Barati, Mahmoud; Joghataei, Mohammad Taghi
Abstract: Cancer as a multifactorial and smart disease is now considered a challenging problem. Despite many investigations on drug discovery, it remains incurable, in part, due to insufficient understanding of its special mechanisms. For the first time, we collaterally investigated the effect of acidosis on the contribution of apoptosis, necrosis, and autophagy in MDA‐MB 231 cells. Our data showed that necrosis, apoptosis, and intracellular reactive oxygen species production drastically decreased from 48 to 72 hr while cell viability and autophagy increased along with a gap between the percentages. Eventually, the decrease of necrosis and apoptosis was related to upregulation of nicotinamide adenine dinucleotide phosphate (NADPH) oxidase and fatty acid synthetase, respectively. It seems that at the early stage of cancer progression, apoptosis is the main mechanism of cell mortality and afterward autophagy would be the main mechanism of cell survival. Therefore, at the acute phase of cancer, apoptotic inducer medications would be effective while at the chronic phase of cancer progression, autophagy inhibitor medication would be added as well. This eventually means that autophagy acts as both cell death and survival mechanisms at the onset of cancer progression with the approach towards cell survival. Besides other unknown cell survival mechanisms are involved in cell viability, except for apoptosis and necrosis inhibition and autophagy improvement. This study reiterates the inefficaciousness of autophagy inhibitor's medication at the onset of disease. It also emphasizes discovering other cell death mechanisms for cancer cell adaptation at the onset of disease with the aim of their targeting in cancer invasion therapy. Abstract : The trends of apoptosis, necrosis, and autophagy in MDA‐MB 231 cells treated by acidic pH medium.